Suicidal Ideation in People With Psychosis Not Taking Antipsychotic Medication: Do Negative Appraisals and Negative Metacognitive Beliefs Mediate the Effect of Symptoms?. (2nd November 2018) - Hutton, Paul; Di Rienzo, Francesca; Turkington, Douglas; Spencer, Helen; Taylor, Peter
Abstract: Between 5% and 10% of people with psychosis will die by suicide, a rate which is 20–75 times higher than the general population. This risk is even greater in those not taking antipsychotic medication. We examined whether negative appraisals of psychotic experiences and negative metacognitive beliefs about losing mental control mediated a relationship between psychotic symptoms and suicidal ideation in this group. Participants were diagnosed with schizophrenia spectrum disorders, antipsychotic-free for 6 months at baseline, and were participating in an 18-month randomized controlled trial of cognitive therapy vs treatment as usual. We conducted a series of mediation analyses with bootstrapping on baseline ( N = 68), follow-up data (9–18 mo; n = 49), and longitudinal data ( n = 47). Concurrent general symptoms were directly associated with suicidal ideation at baseline, and concurrent negative symptoms were directly associated with suicidal ideation at 9–18 months. Concurrent positive, negative, general, and overall symptoms were each indirectly associated with suicidal ideation via negative appraisals and/or negative metacognitive beliefs, at baseline and 9–18 months, except for negative symptoms at baseline. Controlling for baseline suicidal ideation and treatment allocation, baseline general symptoms were indirectly associated with later suicidal ideation, via baseline negative appraisals and negative metacognitive beliefs. Baseline negative metacognitive beliefs also had a direct association with later suicidal ideation. These findings suggest the clinical assessment of suicidal ideation in psychosis may be enhanced by considering metacognitive beliefs about the probability and consequences of losing mental control.